pH-Control Problems of Wastewater Treatment Plants - Alwan, G. M. (Al-Khwarizmi Engineering Journal, 2018)
Experimental investigations have been carried out to investigate the pH-control problems of industrial electroplating wastewater treatment plants. The accurate and sensitive PID control system could treat most problem and disturbances in the normal operation of the water treatment. However, conventional treatment was replaced by proprietary treatment agent called a QUASIL which was found to be more effective for a wide range of pH.